Storylines from Newcomers’ Perspectives: The Complexities of Learning Mathematics in a Norwegian Introductory Class - Shanthi Gretta Pasanha; Annica Andersson; Beth Herbel-Eisenmann; Anita Movik Simensen (Education Sciences)
This paper investigates storylines from newcomers’ perspectives on their experiences of learning mathematics in an introductory mathematics classroom setting in Norway. We engaged in participatory research at a school over time. The data in this article come from observations and conversational interviews. Positioning theory guided our analysis in identifying storylines and related positionings. Our analysis provided us with the following four storylines: (1) newcomers find mathematics easy because they are also learning a new language; (2) newcomers experience tensions when learning mathematics in a new language; (3) newcomers find math teachers extra kind and find that they extend their help to them more than usual; (4) newcomers seek alternative resources for learning advanced mathematics. The identified storylines serve as a valuable resource to understand the newcomers’ wishes and desires for their mathematics education in a context of not yet knowing the language of instruction and educational culture. We recommend listening to newcomers’ perspectives of their experiences and recognizing the strengths they bring to the classroom to understand how they navigate their situation while learning mathematics in multilingual mathematics learning settings.